Price transmission analysis using threshold models: An application to local rice markets in Benin and Mali - Fiamohe, R.; Seck, P.A.; Alia, D.Y.; Diagne, A. (Springer, 2013)
In most African countries, spatial dispersion of production and consumption often results in high transaction costs that prevent farmers from accessing markets and causes asymmetry in price transmission. The objective of this study was to provide the baseline information on local rice price transmission between paired producer and consumer markets in Benin and Mali. To achieve this, we used Enders and Siklos’s threshold models on monthly price series from 2000 to 2010 to examine the nature of price transmission between selected markets in the surplus zones and the nearest important consumption markets. The results for Benin indicated that price transmission between markets in the surplus zone and the consumption markets was asymmetric, probably because of the prevalence of high transaction costs. These results showed that increases in price in the surplus-zone market were more quickly transmitted to the consumer market than decreases in price. Conversely, the results for Mali indicated symmetric price transmission between the market in the surplus zone and the consumer market, suggesting the prevalence of lower transaction costs. These results highlight the need for policies aiming to lower transaction costs observed in selected local rice markets in Benin. Specific policies, such as investment in public infrastructure, e.g. roads, could promote the vertical integration of local rice production with marketing. This would be crucial to achieving rice farmers’ food security and hence their wellbeing.